2001
DOI: 10.1038/labinvest.3780307
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Protects against Neuropathology Induced by a High-Fat Diet and Maintains the Integrity of the Blood-Brain Barrier during Aging

Abstract: SUMMARY:The present study provides evidence that chronic intake of a high-fat diet induces a dramatic extravasation of immunoglobulins, indicating alterations in blood-brain barrier (BBB) functioning, in the brains of apolipoprotein E (apoE)-knockout mice, but not of C57Bl/6 control mice. Using sodium fluorescein as a marker for the permeability of the BBB, we found additional support for age-related disturbances of BBB function in apoE-knockout mice. Behavioral analysis of apoE-knockout mice compared with C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 37 publications
1
48
0
2
Order By: Relevance
“…It has been shown that female ApoE KO mice display greater cognitive impairment than male ApoE KO mice (Raber et al, 1998), a result we have replicated here. Importantly, the impairment in the female ApoE KO mice was completely rescued in the female bEKO mice.…”
Section: )Abnϭ22apoe3/e3supporting
confidence: 78%
See 2 more Smart Citations
“…It has been shown that female ApoE KO mice display greater cognitive impairment than male ApoE KO mice (Raber et al, 1998), a result we have replicated here. Importantly, the impairment in the female ApoE KO mice was completely rescued in the female bEKO mice.…”
Section: )Abnϭ22apoe3/e3supporting
confidence: 78%
“…In peripheral tissues, ApoE is expressed primarily by the liver and released into the blood. In the brain, ApoE is expressed primarily by astrocytes, but can also be expressed by neurons and microglia during cell stress or injury (Pitas et al, 1987;Stone et al, 1997;. Typically, ApoE cannot pass through the BBB (Björkhem et al, 1998); thus, the two pools of ApoE are largely separate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From animal models, proinflammatory cytokines, such as TNF-α, are known to disturb inter-endothelial cell-cell connections and thereby cause BBB permeability [19]. This makes TNF-α transgenic mice [31] and ApoE -/-mice brains [27,29,30], ideal test models to investigate if they share common oxidative stress from an intrinsic biological (proinflammatory cytokine) stressor. We first established that the leaky BBB was restricted to the cerebellum and not the cerebral microvessels in both TNF-α transgenic and ApoE -/-mice brains.…”
Section: Discussionmentioning
confidence: 99%
“…The genetically modified apolipoprotein E knockout (ApoE -/-) mouse is a good example, in order to determine the effects of peripheral infection on a host undergoing high intrinsic stress, due to the constitutive expression of the proinflammatory cytokine, TNF-α [21,22], lipid peroxidation [23], impaired immuno-modulatory function in macrophages and innate/adaptive immune responses [24][25][26]; and impaired cerebellar microvessels [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%